CULTURE PRODUCTIVITY OF Daphnia magna FED WITH QUAIL DROPPINGS (Coturnix coturnix) - Santoso, Marhaendro; Belagama, Ganal Andherpati; Nugrayani, Dewi; Pramono, Taufik Budhi (Aquaculture Department, University of Mataram, 2023)
This research aimed to know the effect of quail manure on an abundance of Daphnia magna. The research method for D. magna was a Completely Randomized Design (CRD) with four settings, each repeated four times, namely the use of P0 (Control without fertilizer), P1 (Quail manure fertilize 1 g/L), P2 (Quail manure fertilize 3 g/L), P3 (Quail manure fertilize 5 g/L). D. magna was cultured for 15 days in a container with a volume of 3 liters. The updated parameters were abundance of D. magna, mortality of D. magna, and water quality. The results were analyzed using ANOVA analysis. The results showed that the highest abundance was in P2 (3g / L), and the lowest was in P0 (control). Water quality during the research was temperature 21-24Â°C, pH 7,5-8,4, DO 6,2-7,8 ppm, and ammonia 0-0,25 mg/L.